21.4% efficiency of perovskite solar cells using BMImI additive in the lead iodide precursor based on carbon nanotubes/TiO2 electron transfer layer. Issue 17 (1st December 2020) - Mohammed, Mustafa K.A.
Abstract: Carbon nanotubes (CNT) are unique one-dimensional structures that have been widely used for enhancing optoelectronic devices because of their fascinating properties. In this work, the impact of multi-walled CNT (MWCNT) on photovoltaic (PV) performance of mesoporous-titanium dioxide (m-TiO2 ) based perovskite solar cells (PSCs) is investigated. First, the incorporation of 1-Butyl-3-methylimidazolium iodide (BMImI) within the lead iodide (PbI2 ) precursor caused suppressing PbI2 residue from perovskite (PVK) film as proved via X-ray diffractometer (XRD). The loading of MWCNT in the m-TiO2 electron transfer layer (ETL) led to the formation of PVK with bigger grains and higher crystallinity with improved light absorbance. The power-conversion efficiency (PCE) of the PSC was remarkably boosted to 21.4% for the device containing 0.2% MWCNT versus 12.5% for the control device without any additives. MWCNT loaded in TiO2 provides a fast charge transfer within the ETL, resulting in an improving in the short circuit current (Jsc) value. This can be assigned to an enhanced band level alignment of the m-TiO2 after the incorporation of MWCNT. Moreover, it is found that the loading of MWCNT into m-TiO2 ETL decreases the hysteresis phenomenon and enhances the heat and humidity stability of the PSCs.